2004
DOI: 10.1021/ic0495517
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structures of Ag(I)-Containing Coordination Polymers and Co(II)-Containing Supramolecular Complex Based on Novel Fulvene Ligands

Abstract: Three new rigid conjugated fulvene ligands L1-L3 were synthesized. L1 and L3 have been prepared by an aroylation reaction of cyclohexyl-substituted cyclopentadienyl anions. L2 was prepared by the reaction of L1 with PhNHNH2 in hot enthanol. Six new coordination polymers, namely [Ag(C25H20N2O2)(ClO4)] x 3.5C6H6 (1), [Ag2(mu-C31H24N4)(eta2-C6H6)(H2O)](ClO4)2 x (C6H6) x (H2O)0.5 (3), [Ag(C31H24N4)]SbF6 x solvate (4), [Ag(C31H24N4)](SbF6)2 x 2C6H6 x CH2Cl2 (5), [Ag(C25H20N2O2)2]SbF6 (6), and [Ag(C25H20N2O2)2]SbF6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 85 publications
6
42
0
Order By: Relevance
“…Previous studies have shown that coordination compounds containing d 10 metal centers such as Cd(II) may exhibit excellent luminescence properties and have potential applications as photoactive materials [24,25]. In the present work, the luminescence of complex 2 and the parent H 2 L compound has been investigated in the solid state at room temperature.…”
Section: Luminescence Propertiesmentioning
confidence: 93%
“…Previous studies have shown that coordination compounds containing d 10 metal centers such as Cd(II) may exhibit excellent luminescence properties and have potential applications as photoactive materials [24,25]. In the present work, the luminescence of complex 2 and the parent H 2 L compound has been investigated in the solid state at room temperature.…”
Section: Luminescence Propertiesmentioning
confidence: 93%
“…Furthermore, the adjacent 2D layers are connected via an additional pair of bbi ligands along the c axis to form the resultant 3D supramolecular architectures with the inter-layer distance of 14.0271(15) Å (Figure 4). From the topological point of view, the 3D structure of 1 can be reduced to a (4,4) 27, 28 The structures of these complexes comprise two equivalent, mutually interpenetrating three-dimensional networks, while polymer 1 forms an open, microporous structure.…”
Section: 17mentioning
confidence: 99%
“…[1][2][3] The key to the successful design of metal-organic coordination polymers is the judicious selection of organic ligand. 4 Recently, polydentate aromatic nitrogen heterocyclic ligands with fivemembered rings have been well-studied in the construction of supramolecular structure for their N-coordinated sites apt to coordinating to transition metals. Similar to six-membered N-heterocyclic ligands, the azole-based five-membered N-heterocyclic ligands, such as imidazoles, triazoles and tetrazoles have been extensively employed in the construction of various coordination polymers with diverse topologies and interesting properties.…”
mentioning
confidence: 99%
“…The luminescence properties of complexes with d 10 metal centers such as Zn(II) and Cd(II) are of interest for their potential application as photoactive materials [16,17]. Therefore, the luminescence of complexes 1 and 2 and the H 2 L reference was investigated in the solid state at room temperature.…”
Section: Luminescence Propertiesmentioning
confidence: 99%